2015
DOI: 10.1007/s00253-015-7192-y
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary formation of gene clusters by reorganization: the meleagrin/roquefortine paradigm in different fungi

Abstract: The biosynthesis of secondary metabolites in fungi is catalyzed by enzymes encoded by genes linked in clusters that are frequently co-regulated at the transcriptional level. Formation of gene clusters may take place by de novo assembly of genes recruited from other cellular functions, but also novel gene clusters are formed by reorganization of progenitor clusters and are distributed by horizontal gene transfer. This article reviews (i) the published information on the roquefortine/meleagrin/neoxaline gene clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…Recently, it has been suggested that some fungal gene clusters can suffer reorganization processes leading to the total or partial loss of some genes (Martín and Liras, 2016). In accordance with this suggestion, it can be hypothesized that the adrB gene originally present in P. chrysogenum was entirely or partially lost in the adr cluster from P. roqueforti .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, it has been suggested that some fungal gene clusters can suffer reorganization processes leading to the total or partial loss of some genes (Martín and Liras, 2016). In accordance with this suggestion, it can be hypothesized that the adrB gene originally present in P. chrysogenum was entirely or partially lost in the adr cluster from P. roqueforti .…”
Section: Resultsmentioning
confidence: 99%
“…MSF proteins are ubiquitous membrane proteins that are responsible for the movement of a wide range of substrates across biological membranes (Quistgaard et al, 2016). In the case of genes encoding for MSF proteins located into fungal biosynthetic gene clusters, it has been suggested that these proteins could be involved in the secretion of the secondary metabolites produced (Martín et al, 2005; Martín and Liras, 2016). Therefore, we tested if adrC could influence andrastin A production and/or secretion.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations